Dark matter searches at the LHC - Klančnik Kunstelj, Maj Leandro (Matrika, 2023)
The existence of dark matter is one of the greatest yet unsolved mysteries in physics. It has for a long time attracted much notice from astronomers, cosmologists, experimental and theoretical particle physicists alike. This article will attempt to provide an approachable overview of dark matter. In the first part we go over the astronomical evidence of dark matter and delve into other motivations for the introduction of new physics. We then consider a number of theoretical explanations, most notably the famous Supersymmetric Models. After establishing a theoretical basis, we describe the experimental setup in the case of the ATLAS detector at the LHC, after which we more deeply discuss some experimental strategies for dark matter searches at the LHC.
Keywords: dark matter; fizika osnovnih delcev; LHC; new physics; nova fizika; particle colliders; physics of elementary particles; pospeševalniki delcev; temna snov